The absolute number of small and diminutive adenomas with high-grade dysplasia is substantially higher compared with large adenomas: a retrospective pooled study - Zhang, Jiancheng; Sun, Huajun; Xiong, Fei; Lei, Shan; Zhou, Guanyu; Xiao, Xun; Liu, Lin; Wang, Pu (Frontiers in Oncology, 2024)
The risk that a large polyp (≥10mm) evolves into high-grade dysplasia (HGD) is relatively high compared to that of a small/diminutive polyp (<10mm). Recently, the detection of small and diminutive polyps has been substantially improved with the advancement of endoscopy. However, further research is needed on the role of the incidence of high-grade dysplasia (HGD) caused by the cooccurrence of small and diminutive polyps in the progression of HGD. In this study, we aim to investigate whether and how the small and diminutive polyps correlate with the incidents of HGD in the population.The pooled data were deeply analyzed from four published randomized controlled trials (RCTs) regarding colon polyp detection. All polyps detected were examined and confirmed by pathologists. The primary outcome was the composition ratio of the HGD polyps in each polyp size category.Results: Among a total of 3,179 patients with 2,730 polyps identified, there were 83 HGD polyps confirmed, and 68 patients had at least one polyp with HGD. The risk of development of HGD was lower for a single small and diminutive polyp compared to that for one large polyp (2.18% vs 22.22%, p<0.0001). On the contrary, the composition ratio for HGD from small and diminutive polyps was significantly higher than that from the large ones (68.67% vs 31.33%, p<0.0001). The combined number of HGD presented a trend to be negatively correlated to size.Our data demonstrated that the absolute number of HGD significantly derives more from small and diminutive polyps than from the large ones, and the collective number of small and diminutive polyps per patient is indicative of his/her HGD exposure. These findings positively provide novel perspectives on the management of polyps, and further may optimize the prevention of colorectal cancer.